Faktor-Faktor Yang Mempengaruhi Pertimbangan Auditor Dalam Mengevaluasi Bukti Audit Pada Kantor Akuntan Publik: Studi Empiris di Jawa Tengah dan DIY - Mulyadi, Mulyadi; TDKW, Yuniatin (STIE AUB Surakarta, 2018)
This study aims to provide empirical evidence that: Analysis of Factors Affecting Auditor Consideration in Evaluating Audit Evidence At KAP Central Java and DIY. The research location used is Public Accounting Firm in Central Java and DIY. The population in this study is the overall auditor who works in Public Accounting Firm in Central Java and and DIY. The technique in sampling is Purposive Sampling. The sample used in this study is 82 auditors. The research instrument was tested by using validity test and reliability test. As for the classical assumption test used normality test, multicolonierity test, heteroscedasticity test and autocorrelation test. The data of this research were analyzed by multiple linear regression and t test. The result of hypothesis analysis is Persuasion on Client's preference, Pressure of Obedience, Audit Experience and Skepticism individually have a positive and significant impact on Auditor Consideration in Evaluating Audit evidence. The result of test of R2 shows variables of Persuasion on Client's preference, Pressure of Obedience, Audit Experience, Skepticism can give 77.4% influence to Auditor's Consideration in Evaluating Audit Audit, while the rest of 22.6% is influenced by other factors not examined, for example competence , professionalism, and task complexity.Keywords: Auditor's Consideration In Evaluating Audit Evidence, Persuasion on Client Preference, Pressure of Obedience, Audit